DK dictionary thesaurus - Dignen, Sheila (Dorling Kindersley, 1999)
A combined dictionary and thesaurus which is arranged alphabetically with more than 15,000 dictionary entries and over 3500 thesaurus entries. This enables the user to look up meanings and discover alternative words at the same time. Each wordfinder thesaurus entry appears after the relevant dictionary entry and is printed in a blue box for easy identification. It is Intended as a reference source for home and school use.